Stochastic Block Model Reveals Maps of In Applied Mathematics Studies Using VOS Viewer - Arifin Karim; Joko Soebagyo; Sigid Edy Purwanto (International Journal of Progressive Mathematics Education, 2021)
Bibliometric analysis is the mapping of research research trends by processing metadata from Google Scolar. The aim is to find out research trends in applied mathematics. The research was conducted on April 30, 2021 through searching the Google Scholar database with the keywords applied mathematics with the publication name journal and the maximum number of results is 500 journals as a sample. Metadata retrieval using the Publish or Perish (POP) application version 7.31. The PoP data were then analyzed descriptively based on the publication year, publisher name, researcher productivity, and journal ranking. To get an accurate map of research developments, PoP data is exported to Exel CSV and Result as RIS file formats. The CSV data was created in a pivot table and the RIS data was analyzed using the VOSViewer (VV) application. The results of the research show that the number of publications of research results in the years 2005-2021 has fluctuated and is mostly published in Elsevier. The most prolific foreign researcher in publishing research results is Biher Bist with 14 articles. The VV visualization shows that the map of the development of applied mathematics research is divided into 5 clusters. Cluster 1 consists of 27 topics, cluster 2 consists of 15 topics, cluster 3 consists of 10 topics, cluster 4 consists of 7 topics, and cluster 5 consists of 3 topics with the most research covering mathematics, paper, problem, solution, system, university, department, science. Â  Analisis bibliometrik merupakan pemetaan tren penelitian penelitian dengan mengolah metadata dari Google Scolar. Tujuannya untuk mengetahui tren penelitian matematika terapan. Penelitian dilakukan pada tanggal 30 April 2021 melalui pencarian database Google Scholar dengan kata kunci matematika terapan dengan nama publikasi jurnal dan jumlah hasil maksimal 500 jurnal sebagai sampel. Pengambilan metadata menggunakan aplikasi Publish or Perish (POP) versi 7.31. Data PoP kemudian dianalisis secara deskriptif berdasarkan tahun penerbitan, nama penerbit, produktivitas peneliti, dan pemeringkatan jurnal. Untuk mendapatkan peta perkembangan penelitian yang akurat, data PoP diekspor ke Exel CSV dan Result sebagai format file RIS. Data CSV dibuat dalam tabel pivot dan data RIS dianalisis menggunakan aplikasi VOSViewer (VV). Hasil penelitian menunjukkan jumlah publikasi hasil penelitian pada tahun 2005-2021 mengalami fluktuasi dan sebagian besar dimuat di Elsevier. Peneliti asing yang paling produktif mempublikasikan hasil penelitiannya adalah Biher Bist dengan 14 artikel. Visualisasi VV menunjukkan peta perkembangan penelitian matematika terapan terbagi menjadi 5 cluster. Cluster 1 terdiri dari 27 topik, cluster 2 terdiri dari 15 topik, cluster 3 terdiri dari 10 topik, cluster 4 terdiri dari 7 topik, dan cluster 5 terdiri dari 3 topik dengan penelitian terbanyak meliputi matematika, makalah, masalah, solusi, sistem, universitas, departemen, sains.